1982
DOI: 10.1104/pp.69.3.575
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Localization of Peptide Hydrolases in Wheat (Triticum aestivum L.) Leaves

Abstract: Protoplasts from 8-to 9-day-old wheat (Triticum aestivum L.) leaves were used to isolate organelles which were examined for their contents of peptide hydrolase enzymes and, in the case of vacuoles, other acid hydrolases. High yields of intact chloroplasts were obtained using both equilibrium density gradient centrifugation and velocity sedimentation centrifugation on sucrose-sorbitol gradients. Aminopeptidase activity was found to be distributed, in approximately equal proportions, between the chloroplasts and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
50
1

Year Published

1985
1985
1997
1997

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 16 publications
(38 reference statements)
2
50
1
Order By: Relevance
“…Peoples et al (24) found that the flag leaf of wheat had two peaks of acid proteinase activity, but only the second peak coincided with the rapid loss of RuBPCase protein. Subsequent work has shown that the vacuoles of wheat ( 14,34), corn (33), barley (9,30), and pineapple (2) leaves contained the major leaf proteolytic activity. The separation of protein substrates from the major hydrolytic enzymes by cellular compartmentation and the differences between attached and detached leaves help explain the difficulties in establishing meaningful correlations between assays for total proteolytic activity and protein degradation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Peoples et al (24) found that the flag leaf of wheat had two peaks of acid proteinase activity, but only the second peak coincided with the rapid loss of RuBPCase protein. Subsequent work has shown that the vacuoles of wheat ( 14,34), corn (33), barley (9,30), and pineapple (2) leaves contained the major leaf proteolytic activity. The separation of protein substrates from the major hydrolytic enzymes by cellular compartmentation and the differences between attached and detached leaves help explain the difficulties in establishing meaningful correlations between assays for total proteolytic activity and protein degradation.…”
Section: Discussionmentioning
confidence: 99%
“…The concentration of other soluble proteins remains quite stable during the time that RuBPCase is disappearing (25). There is now good evidence that chloroplasts contain proteinases that can degrade their protein constituents (5,28,31,34) and degrade their Chl as well (18). Recent reports show a sequential loss of chloroplast constituents and chloroplast numbers; both RuBPCase protein and activity disappeared faster than chloroplast number in senescing leaves of wheat (16,36) and barley (19).…”
mentioning
confidence: 99%
“…Isolated chloroplasts from barley (3) and soybean (19) were capable of degrading RuBPCase4; an ATP-dependent proteolytic activity was located in thylakoids from pea chloroplasts (8,11), and one endoprotease and three APs were found in the stromal fraction of pea chloroplasts (9); endoproteolytic activity against RuBPCase was found in the stromal fractions of chloroplasts from barley leaves (22,23) Nettleton et al (17) and Tang and Huffaker (23) found proteolytic activities associated with the thylakoid fractions of chloroplasts from wheat and barley leaves, respectively, capable of degrading RuBPCase. In wheat, 50% of the AP activity was localized in chloroplasts with the remainder in the cytoplasm (30).…”
mentioning
confidence: 99%
“…AP activity was assayed spectrophotometrically (20,30) with each assay consisting of 0.8 ml of 12.5 mm K-phosphate buffer (pH 6.8), 0.1 ml of 10 mM L-aa-/3-NA substrate, and 0.1 ml of enzyme source (total volume, 1 ml). NADPH-dependent TPDH was assayed according to Heber et aL (6).…”
mentioning
confidence: 99%
“…The vacuoles are the main site of protease deposition (3,6,10,18,25,(30)(31)(32). This conspicuous cell compartment was shown to be directly involved in the breakdown of storage proteins during germination in seeds (24) (19,20) and to contain a specific protease directed towards the light subunit of RuBP carboxylase (27).…”
Section: Introductionmentioning
confidence: 99%